Targeting GABAAR-Associated Proteins: New Modulators, Labels and Concepts - Khayenko, Vladimir; Maric, Hans Michael (Frontiers in Molecular Neuroscience, 2019)
γ-aminobutyric acid type A receptors (GABAARs) are the major mediators of synaptic inhibition in the brain. Aberrant GABAAR activity or regulation is observed in various neurodevelopmental disorders, neurodegenerative diseases and mental illnesses, including epilepsy, Alzheimer’s and schizophrenia. Benzodiazepines, anesthetics and other pharmaceutics targeting these receptors find broad clinical use, but their inherent lack of receptor subtype specificity causes unavoidable side effects, raising a need for new or adjuvant medications. In this review we introduce a new strategy to modulate GABAeric signaling: Targeting the intracellular protein interactors of GABAARs. Of special interest are scaffolding, anchoring and supporting proteins that display high GABAAR subtype specificity. Recent efforts to target gephyrin, the major intracellular integrator of GABAergic signaling, confirm that GABAAR-associated proteins can be successfully targeted through diverse molecules, including recombinant proteins, intrabodies, peptide-based probes and small molecules. Small-molecule artemisinins and peptides derived from endogenous interactors, that specifically target the universal receptor binding site of gephyrin, acutely affect synaptic GABAAR numbers and clustering, modifying neuronal transmission. Interference with GABAAR trafficking provides another way to modulate inhibitory signaling. Peptides blocking the binding site of GABAAR to AP2 increase the surface concentration of GABAAR clusters and enhance GABAergic signaling. Engineering of gephyrin binding peptides delivered superior means to interrogate neuronal structure and function. Fluorescent peptides, designed from gephyrin binders, enable live neuronal staining and visualization of gephyrin in the post synaptic sites with nanometer resolution. We anticipate that in the future, novel fluorescent probes, with improved size and binding efficiency, may find wide application in super resolution microscopy studies, enlightening the nanoscale architecture of the inhibitory synapse. Broader studies on GABAAR accessory proteins and the identification of the exact molecular binding interfaces and affinities will advance the development of novel GABAAR modulators and following in-vivo studies will reveal their clinical potential as adjuvant or stand-alone drugs.